Wide-field endoscopic submucosal dissection for the treatment of Barrett’s esophagus neoplasia - Omae, Masami; Hagström, Hannes; Ndegwa, Nelson; Vieth, Michael; Wang, Naining; Vujasinovic, Miroslav; Baldaque-Silva, Francisco (Endoscopy International Open, 2021)
Background and study aims Implementation of endoscopic submucosal dissection (ESD) for the treatment of Barrett’s esophagus neoplasia (BEN) has been hampered by high rates of positive margins and complications. Dissection with wider margins was proposed to overcome these problems, but was never tested. We aim to compare Wide-Field ESD (WF-ESD) with conventional ESD (C-ESD) for treatment of BEN.Patients and methods This was a cohort study of all ESDs performed in our center during 2011 to 2018. C-ESD was the only technique used before 2014, with WF-ESD used beginning in 2014. In WF-ESD marking was performed 10 mm from the tumor margin compared to 5 mm with C-E.Results ESD was performed in 90 cases, corresponding to 74 patients, 84 % male, median age 69. Of these, 22 were C-ESD (24 %) and 68 were WF-ESD (76 %). The en bloc resection rate was 95 vs 100 % (ns), the positive lateral margin rate was 23 % vs 3 % (P  < 0.01), the R0 rate was 73 % vs 90 %, and the curative resection rate was 59 % vs 76 % in the C-ESD and WF-ESD groups, respectively, (both P > 0.05). The procedure speed was 4.4 and 2.3 (min/mm) in the C-ESD and WF-ESD groups (P < 0.01), respectively. WF-ESD was associated with less post-operative strictures, 6 % vs 27 % (P = 0.01), with no local recurrence but no significantly reduced risk of metachronous recurrence (Hazard Ratio = 0.46, 95 %CI = 0.14–1.46), during a follow-up of 13.4 and 9.4 months in the C-ESD and WF-ESD cohorts, respectively.Conclusions WF-ESD is associated with a reduction in positive lateral margins, faster dissection, and lower stricture rates. Further prospective, multicenter studies are warranted to evaluate its role in clinical practice.